Introduction to the Special Issue: Demand and Supply of Islamic Religious Guidance in Post-Communist Eurasia: Between Online and Offline - Račius, Egdūnas (Journal of Muslims in Europe, 2026)
This special issue is intended to provide insights into the evolving dynamics in offline and online Islamic religious guidance and practice in Eurasia. The four articles share a common focus on the role of digital and online environments in shaping Islamic religious knowledge transmission and community engagement within Muslim minority contexts in CEE countries (Lithuania, Hungary and Poland) and also the CIS.